Historien - eller om at læse tiden - Chartier, Roger (Slagmark - Tidsskrift for idéhistorie, 2018)
In this article the author reflects on the supposed ‘crisis of history’ which obsessed historians in the 1980s and 1990s. From these reflections the article seeks to provide answers to questions of ‘what history is’ between the definitions as narrative and knowledge. By analyzing the ideas of many intellectual historians such as Michel de Certeau and Reinhard Koselleck, Chartier contextualizes fundamental historiographical knowledge with more recent trends such as microhistory and globalism in order to arrive at a proposal of history as specifically capable of recognizing and articulating different times imbricated in historical moments.